Relevance for chronopharmacology in practical medicine - Lemmer, Björn (Seminars in perinatology, 2000)
Nearly all functions of the body, including those influencing pharmacokinetic parameters, such as drug absorption and distribution, drug metabolism, and renal elimination display significant daily variations. Also, the onset and symptoms of diseases such as asthma attacks, coronary infarction, angina pectoris, stroke, and ventricular tachycardia are circadian-phase dependent. Asthma attacks predominatly occur around 4 o'clock at night. Blood pressure and heart rate in normotensives and essential (primary) hypertensive patients display highest values during daytime followed by a nightly drop and an early morning rise. In about 70% of forms of secondary hypertension, however, this rhythmic pattern is abolished or even reversed exhibiting nightly peaks in blood pressure. Similar findings were obtained in children. This form of hypertension is accompanied by increased end organ damages. These observations call for a circadian time-specified drug treatment. In nocturnal asthma unequal dosing of antiasthmatic drugs with a higher/single evening dose is recommended. In secondary hypertension not only the elevated blood pressure must be reduced but the disturbed blood pressure profile should be normalized, too, possibly best achieved by evening dosing. Pharmacokinetics may also not be constant within 24 hours of a day as shown for cardiovascular active drugs, antiasthmatics, anticancer drugs, psychotropics, anlagesics and local anesthetics, antibiotics to mention but a few. Far more drugs were shown to display significant daily variations in their effects even after chronic application or constant infusion. Because circadian rhythms undergo maturation with development, drug therapy in children can/may also be modified by circadian time of drug dosing as shown for anticancer drugs. In conclusion, there is clear evidence that the dose/concentration-response relationship of drugs can be significantly dependent on the time of day. Thus, circadian time has to be taken into account as an important variable influencing a drug's pharmacokinetics and/or its effects or side effects.
Available online 11 May 2006
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 14.04.2022